2021
DOI: 10.1111/1467-9566.13391
|View full text |Cite
|
Sign up to set email alerts
|

Searching for diagnostic certainty, governing risk: Patients' ambivalent experiences of medical testing

Abstract: Diagnosis is pivotal to medicine's epistemic system: it serves to explain individual symptoms, classify them into recognizable conditions and determine their prognosis and treatment. Medical tests, or investigative procedures for detecting and monitoring disease, play a central role in diagnosis. While testing promises diagnostic certainty or a definitive risk assessment, it often produces uncertainties and new questions which call for yet further tests. In short, testing, regardless of its specific applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In this context, echoing concerns of other nonparticipants across screening programmes (e.g., Berg‐Beckhoff et al; Maclean et al), 54,55 engaging in screening risked ‘making’ AF and opening Pandora's box of ‘trouble’. This was not irrational: testing for a condition they did not think they had (but that they recognised could be identified by screening) would create unhelpful awareness of problems in their body and disrupt their health 56 . Moreover, their acceptance that they would die ‘when their time has come’ as Davison et al 57 found (and since found in screening 50 ), exposed the mirage of screening and preventative health practice in halting death 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, echoing concerns of other nonparticipants across screening programmes (e.g., Berg‐Beckhoff et al; Maclean et al), 54,55 engaging in screening risked ‘making’ AF and opening Pandora's box of ‘trouble’. This was not irrational: testing for a condition they did not think they had (but that they recognised could be identified by screening) would create unhelpful awareness of problems in their body and disrupt their health 56 . Moreover, their acceptance that they would die ‘when their time has come’ as Davison et al 57 found (and since found in screening 50 ), exposed the mirage of screening and preventative health practice in halting death 58 .…”
Section: Discussionmentioning
confidence: 99%
“…This was not irrational: testing for a condition they did not think they had (but that they recognised could be identified by screening) would create unhelpful awareness of problems in their body and disrupt their health. 56 Moreover, their acceptance that they would die ‘when their time has come’ as Davison et al 57 found (and since found in screening 50 ), exposed the mirage of screening and preventative health practice in halting death. 58 Together these factors rebalanced perspectives to place more weight on the effort of participating against the benefit of addressing future ill health.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when diagnosed with a chronic or fatal illness, individuals experience BD as Liamputtong and Suwankhong (2015) suggest. However, in this context, individuals experience diagnosis as relief and redemption, as Bury also suggests (on diagnosis as relief see also Pienaar & Petersen, 2021). 2 For some researchers, BD is perceived as a vertical line that separates life in two (before and after the onset of a disease), and for some others such as Valasaki (2022), BD is a repetitive process experienced, every time new symptoms appear.…”
Section: Experiences and Challenges Prior And During Diagnosismentioning
confidence: 99%
“…Conflicting expectations and interests in these healthcare practices can fuel tension and ambivalence on both an individual (patient and/or professional) and structural (in practices and/or guidelines) level. Literature on ambivalence in healthcare has pointed towards those experiences of patients and involved healthcare professionals, in relation to ethical dilemmas as well as to specific health technologies and diagnoses (17)(18)(19)(20)(21)(22). Work on ambivalence in research contexts, including genetic research, has showed how scientific 'norms' can be oppositional, situated and fluid in nature and how this ambivalence is pivotal in science-making and understanding knowledge transformations (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%